Dresden - Unterwegs in Elbflorenz - Groschopp, Richard; Marten, Walter; Bohm, Karl-Heinz; Fischer, Heinz; Sobiczewski, Heinz; Belz, Uwe; Thorndike, Annelie; Hübel, Wernfried (Icestorm, 2021)
Auf dieser DVD finden Sie Original-Dokumentationen der DEFA aus den Jahren 1946 bis 1985 über "Elbflorenz". [Cover]
Keywords: DVD-Video